Good practice in reaching and treating refugees in addiction care in Germany - a Delphi study - Panagiotis Stylianopoulos; Laura Hertner; Andreas Heinz; Ulrike Kluge; Ingo Schäfer; Simone Penka (BMC, 2024)
Abstract Background Health and adequate access to health care are human rights. Refugees are at risk for substance abuse. Despite the known structural and personal risk factors for abuse, refugees in Germany continue to face barriers to adequate addiction prevention and care, which is a violation of the fundamental human right to health care. The question arises as to how barriers for refugees in reaching addiction services and care can be overcome. In the presented study, strategies for good practices to deconstruct these barriers were identified. Method A total of 21 experts participated in a three-round, consensus-oriented Delphi-Process. The experts represented five different fields: addiction care services, including specialized programs for women, refugee aid services, academia, policy-making and immigrants' self-help services. Results The Delphi-Process generated 39 strategies of good practice summarized in 9 major categories: Care System, Framework Conditions, Multilingualism, Information and Education, Access, Service-Level, Employee-Level, Employee-Attitudes and Networking. Conclusion In order to guarantee human rights regarding health and adequate access to health care for refugees, institutional barriers limiting access to prevention and treatment programs for addictive disorders must be abolished. The identified good practice strategies for Germany, if widely implemented, could contribute to this aim. By opening up prevention and treatment facilities for refugees, other marginalized groups could also benefit. While some of the strategies need to be implemented at the institutional level, political steps are also required at the system level including, e.g. financing of adequate translation services.